The DiAMOND trial protocol: a randomised controlled trial of two decision aids for mode of delivery among women with a previous caesarean section [ISRCTN84367722] - Montgomery Alan A (BMC, 2004)
Abstract Background Caesarean section (CS) has become an increasingly common method of delivery worldwide, rising in the UK from 9% of deliveries in 1980 to over 21% 2001. This increase, and the question of whether CS should be available to women on request, has been the subject of considerable debate, and national reports and guidelines have specifically highlighted the importance of patient choice in the decision making process. For women who have already experienced CS, the UK National Institute of Clinical Excellence recommends that the decision should consider maternal preferences and priorities in addition to general discussion of the overall risks and benefits of CS. Decision aids for many different medical treatment and screening decisions have been developed and evaluated, but there is relatively little evidence for the use of decision aids for choice of mode of delivery among women with a previous CS. The aim of the study is to evaluate two interventions to assist decision making about mode of delivery among pregnant women with one previous CS. Methods/design Women with one previous CS are recruited to the trial during their booking visit at approximately 12-20 weeks' gestation in participating maternity units in Bristol, Weston and Dundee. Using central randomisation, women are allocated to one of three arms: information programme and website; decision analysis; usual care. Both interventions are computer-based, and are designed to provide women with detailed information about the potential outcomes for both mother and baby of planned vaginal delivery, planned CS and emergency CS. The decision analysis intervention additionally provides a recommended 'preferred option' based on maximised expected utility. There are two primary outcomes (decisional conflict and actual mode of delivery), and five secondary outcomes (anxiety, knowledge, perceptions of shared decision making; satisfaction with decision making process, proportion of women attempting vaginal delivery). Primary follow up for the questionnaire measures is at 36-37 weeks' gestation, and a total of 660 women will be recruited to the study. The primary intention-to-treat analyses will comprise three pair-wise comparisons between decision analysis, information and usual care groups, for each of the two primary outcomes. A qualitative study will investigate women's experiences of the decision making in more depth, and an economic evaluation from the perspective of the NHS will be conducted. Discussion Provision of information to women facing this decision appears variable. The DiAMOND study aims to inform best practice in this area by evaluating the effectiveness of two interventions designed to aid decision making.